Consequence of Gender and Job Characteristics with Normative Commitment - Shrestha, Deepmala (Journal of Nepalese Business Studies, 2012)
The aim of this study is to investigate the existence of relationships between components of psychological climate including gender issue, autonomy, work pressure, skills used and normative commitment. This study shows that, for a sample 109 Nepalese Commercials Banks employees, one component (Normative) of organizational commitment are predicted by two characteristics that influence the commitment (personal, and Job) affected to organizational performance. Implications for future research are discussed. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page : 100-114 Uploaded date: July 8, 2012